Kesatuan Agama-agama dan Kearifan Perennial dalam Perspektif Tasawuf - Armia Armia (AL-TAHRIR, 2013)
Abstract: All religions, if we try to find their core teachings, we will find the same messages, namely the realization of peace, goodness, and happiness to mankind. No religion teaches violence and savagery. This confirms that theologically religion is very much interested in the realization of human well-being in life. Thus, peace must be a meeting point for all religions to implement in social life. This paper explored the Sufi’s view of the nature of God, religion, and the perennial wisdom based on the principle of spirituality and love (mahabbah).